Arthroscopy-assisted osteosynthesis of triplane fracture - case - Malý, Jakub; Kopp, Lubomír; Edelmann, Karel (Úrazová chirurgie, 2018)
Triplane fractures are rare injuries of the transitional period of skeletal maturation, where the physeal growth plate is not yet fully closed. Computed tomography plays an essential role in the diagnostics, the most important procedure in the therapy of displaced fractures are a reduction of the articular surface performed under visual control and stable fixation with interfragmetary compression. Arthroscopy-assisted osteosynthesis fulfils the requirements of being a minimally invasive procedure, while preserving the possibility of visual control of the reduction, and seems to be a suitable alternative to other techniques. Anatomical reduction of the articular surface is crucial for proper healing without deformities, growth disturbances and resulting complications in adolescence. A disadvantage of the arthroscopically assisted osteosynthesis lies in its equipment demands and the required level of erudition of the surgical team. Hence, these injuries shall be centralised at specialized departments.